Transanal minimal invasive surgery for rectal lesions: should the defect be closed?. (May 2015) - Hahnloser, D.; Cantero, R.; Salgado, G.; Dindo, D.; Rega, D.; Delrio, P.
Abstract: Aim: Transanal minimal invasive surgery (TAMIS) of rectal lesions is increasingly being used, but the technique is not yet standardized. The aims of this study were to evaluate peri‐operative complications and long‐term functional outcome of the technique and to analyse whether or not the rectal defect needs to be closed. Method: Consecutive patients undergoing TAMIS using the SILS port (Covidien) and standard laparoscopic instruments were studied. Results: Seventy‐five patients (68% male) of mean age 67 (± 15) years underwent single‐port transanal surgery at three different centres for 37 benign lesions and 38 low‐risk cancers located at a mean of 6.4 ± 2.3 cm from the anal verge. The median operating time was 77 (25−245) min including a median time for resection of 36 (15−75) min and for closure of the rectal defect of 38 (9−105) min. The defect was closed in 53% using interrupted (75%) or a running suture (25%). Intra‐operative complications occurred in six (8%) patients and postoperative morbidity was 19% with only one patient requiring reoperation for Grade IIIb local infection. There was no difference in the incidence of complications whether the rectal defect was closed or left open. Patients were discharged after 3.4 (1−21) days. At a median follow‐up of 12.8 (2−29) months, the continence was normal (Vaizey score of 1.5; 0−16). Conclusion: Transanal rectal resection can be safely and efficiently performed by means of a SILS port and standard laparoscopic instruments. The rectal defect may be left open and at 1 year continence is not compromised.